Whole‐of‐community invertebrate rewilding: Leaf litter transplants rapidly increase beetle diversity during restoration. Issue 2 (26th December 2022) - Contos, Peter; Murphy, Nicholas P.; Gibb, Heloise
Abstract: Restoration of degraded areas is now a central tool in humanity's response to continued species‐loss. However, restoration projects often report exceedingly slow or failed recolonization of fauna, especially dispersal‐constrained groups such as invertebrates. Active interventions via reintroducing or "rewilding" invertebrates may assist recolonization and speed up restoration of communities toward a desired target. However, invertebrate rewilding is rarely implemented during ecological restoration. Here, we studied the efficacy of invertebrate rewilding as a means of reintroducing dispersal‐constrained species and improving diversity and compositional similarities to remnant communities during restoration. Rewilding was conducted by transplanting leaf litter and soil, including associated communities of invertebrates from species rich remnant sites into species poor, and geographically isolated, revegetated farmland sites. We sampled pre‐ and post‐rewilding invertebrate communities in remnant, rewilded revegetation, and control revegetation sites. We analyzed morphospecies richness, abundance, community composition, and modeled morphospecies traits (dispersal method/trophic guild) using a Hierarchical Modelling of Species Communities approach to determine which biological properties facilitated establishment. Beetle (Coleoptera) morphospecies richness increased rapidly in rewilded sites and was indistinguishable from remnant communities as early as 7 months post‐rewilding. Beetle community similarity in the rewilding sites significantly deviated from the control sites 27 months post‐rewilding, however remnant communities remained distinct over the study timeframe. Establishment success varied as other taxa did not respond as consistently as beetles within the study timeframe. Furthermore, there were no discernible shifts in dispersal traits in rewilded sites. However, predatory morphospecies were more likely to establish post‐rewilding than other trophic groups. Our results demonstrate that the relatively simple act of transplanting leaf litter can result in comparatively large increases in morphospecies richness during restoration in a short timeframe. We advocate methodologies such as ours should be adopted more frequently to address failed community restoration as they are cost‐effective and can be easily applied by practitioners in various restoration settings. However, further efficacy tests (e.g., varying the number of rewilding events) and longer study timeframes are needed to ensure effectiveness for a broader range of invertebrate taxa and ecosystems.